Lelang Tanah Pusako Tinggi Yang Tidak Bersertifikat di Ranah Minang - Mhd Khadafi Abdullah (Journal of Global Legal Review, 2024)
This article aims to examine and analyze the implementation of the execution of the decision in case number: 22/Pdt.G/2022/PN Pmn which has been confirmed by the decision of the Padang High Court with registration number: 82/PDT/2023/PT PDG. The decision in case number: 22/Pdt.G/2022/PN Pmn as confirmed by the decision of the Padang High Court with registration number: 82/PDT/2023/PT PDG has provided legal certainty between the plaintiff and the defendant, so that the plaintiff is the winning party. requested the execution of the decision from the court, which is registered in the execution request number: 3/Pdt.Eks/2024/PN.Pmn. The Pariaman District Court in its decision ordered the defendant to return the gold loan to the plaintiff in the amount of 123 (one hundred and twenty three) gold plus 2 (two) ringgits of genuine American plain gold. In the process of carrying out the anmaning trial, the defendant was unwilling and unable to return the borrowed gold as ordered by the court, so the Court forced the defendant to return the loan in the form of executing an auction for the object of debt collateral, in the form of Pusako Tinggi rice fields belonging to the defendant. In this paper, the author uses normative juridical research, namely legal research which places law as a building system of norms. The norm system in question is about principles, norms, rules of laws and regulations, court decisions, agreements and doctrines (teachings). This research uses primary legal materials such as: 1. Pariaman District Court decision number: 22/Pdt.G/2022/PN Pmn, 2. Padang High Court decision number: 82/PDT/2023/PT PD, and 3. Petition for the plaintiff's execution /applicant number: 3/Pdt.Eks/2024/PN.Pmn. as well as secondary legal materials consisting of books or legal journals containing basic principles (legal principles), views of legal experts (doctrine), results of legal research, legal dictionaries and legal encyclopedias related to the subject matter. Pagang gadai in Ranahminang is still alive and is still practiced among Minangkabau society, even though the land being pawned is pusako high land belonging to the people who pawned it and does not yet have a certificate of ownership, the implementation of the execution auction for the object of the pledge collateral can be carried out in the form of an execution auction for the object collateral for the debts and receivables. Even though the mortgaged Pusako Tinggi land does not yet have a certificate, a face-to-face auction can be executed and a certificate of ownership can still be issued in the name of the auction winner by referring to the minutes of the auction issued by KPKNL, court decisions that have permanent legal force, as well as certificates issued. by the Village / Subdistrict Office where the object of collateral for debts and receivables is located to be registered at the National Land Agency office to issue a certificate of ownership.